2021
DOI: 10.1016/j.ejrad.2021.109879
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of assessment of skeletal muscle mass on a single cross-sectional image at the level of the fourth thoracic vertebra

Abstract: Background: Skeletal muscle mass (SMM) determined on computed tomography (CT) is emerging as a novel imaging biomarker. Cross-sectional area (CSA) of SMM at the level of the third lumbar vertebra (L3) on abdominal imaging is considered the clinical reference standard for measuring SMM. In certain patient groups, such as those with oncological or non-oncological lung disease like COVID-19, a chest CT may be available while an abdominal CT is not. The purpose of this study was to investigate whether determining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
0
15
1
Order By: Relevance
“…In the setting of COVID-19, it became evident that fat tissue assessment and the analysis of muscle mass, typically analyzed in the lumbar region on abdominal CT scans, must be validated with surrogates on thoracic CT acquisitions, since this quickly became the gold standard to assess COVID-19 disease severity. One report from a Dutch study group has indicated that skeletal muscle mass determined on a thoracic CT scan appeared to correlate well to measurements on the lumbar region on scans belonging to the same patient [ 15 ]. However, the role of various fat-tissue and muscle mass measurements on thoracic CT scans in predicting a worse outcome has yet to be clearly defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the setting of COVID-19, it became evident that fat tissue assessment and the analysis of muscle mass, typically analyzed in the lumbar region on abdominal CT scans, must be validated with surrogates on thoracic CT acquisitions, since this quickly became the gold standard to assess COVID-19 disease severity. One report from a Dutch study group has indicated that skeletal muscle mass determined on a thoracic CT scan appeared to correlate well to measurements on the lumbar region on scans belonging to the same patient [ 15 ]. However, the role of various fat-tissue and muscle mass measurements on thoracic CT scans in predicting a worse outcome has yet to be clearly defined.…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent the need for interleukin-6, which might not be part of the biological armamentarium of each hospital, mNUTRIC excludes its value from the calculation formula, providing non-inferior risk assessment [ 14 ]. Indicators of malnutrition and sarcopenia derived from standard thoracic CT scans, such as fat tissue amount and disposition, muscle mass, or muscle density were also analyzed in the setting of COVID-19, with most protocols aiming to extrapolate data typically measured on abdominal imaging [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This therefore led to a poorer reproducibility as it was not clear as to where the boundaries of the muscles around the scapula and arm might be. Previous studies encountered a similar such problem and overcame this by including only the pectorals, intercostals and muscles of the back in their CSA measurements (20,21). The variation of the partial exclusion of the muscles seen in the scans at T4 indicates that this level may not be best as the SMI measures would not be reproducible if a patient was to have subsequent scans.…”
Section: Discussionmentioning
confidence: 99%
“…CSMA at level Th4 strongly correlates with L3 CSMA (r = 0.791). A multivariate model (prediction formula) incorporating the patient characteristics arm positioning (downwards or upwards), age, sex, and weight achieved an even stronger correlation (r = 0.856) ( 47 ). It can be concluded that CSMA measured at these levels is a feasible alternative to measurements at L3, particularly when assessment at level C3 is not possible.…”
Section: Sarcopeniamentioning
confidence: 99%